The tides of reform revisited: patterns in making government work, 1945-2002 - Light, Paul C. (2006)
The past six decades have witnessed acceleration in both the number and variety of major administrative reform statutes enacted by Congress. This increase can be explained partly by the increased involvement of Congress, a parallel decrease in activity and resistance by the presidency, and heightened public distrust toward government. At least part of the variation in the tides or philosophies a reform involves a "field of dreams" effect in which the creation of new governmental structure during the 1940s, 1950s, and 1960s generated increased interest in process reforms. However, part of the acceleration and variety of reform appears to be related to the lack of hard evidence of what actually works in improving government performance. Measured by federal employees' perceptions of organizational performance, what matters most is not whether organizations were reformed in the past, but whether organizations were reformed in the past, but whether organizations need reform in the future and can provide essential resources for achieving their mission. - Reproduced.
Keywords: Administrative reform